Proyecto de implementación de una agencia de producción y diseño audiovisual en la ciudad de Guayaquil - Lucas Proaño, Evelyn Janeth (2009)
In the present project it is realized a technical, market and financial feasibility study for the implementation of a production and audiovisual design agency in Guayaquil, which offers to the local market an innovator alternative, which integrates the graphic design and audiovisual production areas in a business model that brings efficiency and dynamism to working processes, reducing the delivery time of the service and optimizing all kind of resources, giving a high quality advertising service that satisfies the client necessities. The purchase of high quality technical equipment for the video production area will allow the agency to compete with the foreign service in the mentioned area of audiovisual production. The financial feasibility study includes a complete detail of the projection of sale incomes, expenses and production costs that we have to incur for the implementation of the agency. All this information will be used to determine the financial feasibility of the project by means of the evaluation methods of NPV and IRR.